HUBUNGAN INDEKS MASSA TUBUH DENGAN SINDROM METABOLIK PADA PENDERITA DIABETES MELLITUS TIPE 2 DI KELURAHAN NAMBANGAN LOR MANGUHARJO - Gevino Valentina Widodo; Zaenal Abidin; Zaenal Abidin (Dian Nuswantoro Semarang, 2020)
Metabolic Syndrome is a set of deviation functions of the body in the form of central obesity, high blood pressure, dyslipidemia (increased levels of cholesterol especially LDL, triglyceride, and low HDL levels), and DM. Metabolic syndrome is basically a pain condition that is characterized by a set of abnormalities with a variety of consequences clinical if allowed to continue and are not addressed early will lead to various degenerative diseases such as diabetes mellitus. The purpose of this study is to determine the relationship between body mass index and metabolic syndrome in type 2 DM patients in Posbindu Sagita Kelurahan Nambangan Lor Manguharjo. This research design is Cross Sectional study. The population of this study are patients with Type 2 DM who is suffering from metabolic syndrome and do not suffer from the metabolic syndrome. The method used is Purposive Sampling technique with the analysis of the Chi-Square Test. The Variables that proved to the Body Mass Index is associated with Metabolic Syndrome in Type 2 DM patients in Posbindu Sagita Kelurahan Nambangan Lor Manguharjo is the value of the ?-value of 0.000 < ? 0.05 RP by 20,0 and (95% CI = 6,5 to 61,1). There is a relationship between Body Mass Index and the Metabolic Syndrome in Patients with Type 2 Diabetes Mellitus. This study shows that respondents who suffer from Type 2 diabetes with obesity are 20 times more likely to suffer from metabolic syndrome than respondents who are not obesity.Keywords: Body Mass Index, Metablic Syndrome, Diabetes Mellitus